Digital Marketing as Behavioral Architecture: How Online Content Designs Internalize Sustainable Consumption Values - Andri Ardhiyansyah; Yusuf Iskandar; Kurniawan Kurniawan; Kristia Kristia (Jurnal Ilmiah Manajemen & Bisnis, 2026)
This study investigates the influence of digitally mediated marketing environments on pro-environmental consumption through indirect perceptual and value-based mechanisms, conceptualizing online content design as an element of broader behavioral architecture within digital decision environments. Drawing on behavioral architecture theory, the research examines how perceived choice architecture and perceived nudging connect digital content design to sustainability-related behavioral tendencies.  Design/methodology/approach: A quantitative cross-sectional survey was administered to 250 active social media users in West Java, Indonesia. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the relationships among online content design, perceived choice architecture, perceived nudging, value internalization, and pro-environmental behavior.  Findings: Online content design does not directly affect pro-environmental behavior. Instead, its influence is mediated by perceived choice architecture and perceived nudging, both of which are positively related to value internalization. Value internalization is identified as the most immediate predictor of pro-environmental behavioral tendencies. Although the model exhibits limited explanatory power, the findings highlight a significant indirect mechanism through which digitally structured environments shape sustainability-related behavior.  Practical implications: Sustainability-oriented digital marketing strategies should focus on structuring digital environments that frame consumer choices and facilitate value-consistent decisions, rather than relying exclusively on persuasive messaging.  Originality/value: This study contributes to digital marketing and sustainability literature by reframing digital marketing as behavioral architecture and identifying value internalization as a central mechanism linking perceived digital environments to pro-environmental behavior.